The Impact Of Tiktok Advertising Content On Consumers’ Purchase Intention In The Post Covid-19 Pandemic In Malaysia - Goh, Bin Wei; Asmaul Husna, Haris Fadzilah (2023)
The objective of this study is to examine the relationship between TikTok advertising content and the purchase intentions of consumers following the Covid-19 pandemic. This study focuses on collecting data by using non-probability convenience sampling by targeting 375 random respondents, which are undergraduate students at University Malaysia Sarawak (UNIMAS), capturing respondents' perceptions of the advertising content on TikTok and their purchase intention. The Uses and Gratifications Theory (UGT) and Theory of Planned Behavior (TPB) serve as the theoretical foundations for this study. The surveys in this research were created using Google Forms and extensively distributed online. This study used a quantitative approach and a cross-sectional research design. Stats SPSS IBM 27 was used for both the collection and analysis of the data. The findings of this research were subjected to an in-depth analysis in which consumers’ purchase intention, entertainment, influencer credibility, sales promotion, and informativeness were all taken into consideration. The study's contribution lies in shedding light on the effectiveness of TikTok as an advertising platform in the context of the post-COVID-19 pandemic in Malaysia. It will provide valuable insights for marketers and businesses seeking to enhance their marketing strategies on TikTok and optimize their reach to potential consumers.